The Landscape of Biologics Drug System in Thailand - Taychakhoonavudh, Suthira; Phoolcharoen, Waranyoo; Pesirikan, Norapath; Tawinwung, Supannikar; Suppipat, Koramit; Luckanagul, Jittima; Suksomtip, Maneewan; Ritthidej, Garnpimol C.; Anantachoti, Puree (Journal of Health Science of Thailand, 2020)
Biologics, breakthrough pharmaceutical products that change the treatment paradigm of many diseases, have unique characteristics that could impact country drug system overall. The aim of this study is to analyse the current situation of biological drugs and gaps in Thailand drug system. We have found that regulations of most biological products in Thailand have been developed slowly and is currently up to international standard and Thailand is currently drafting a new cell therapy act to better regulate advanced therapy medicinal products. While regulations of biologics are not a major concern, access to innovative biologics that are high cost is still an issue. Strengthening research and development of biologics in the country is a key activity done by the Royal Thai Government to lower the cost, improve accessibility and boost Thailand economic growth while innovative pricing mechanisms for high-cost drugs is utilized as a short-term strategy to increase access. The infrastructure of the supply chain of the drug is largely well-established through existing vaccine cold chain system. Human resources development for every sector along the value chain of the biologics drug system is, however, an urgent issue and should be addressed to strengthen the biologics drug system in Thailand.